NATURAL LIGHTING’S CONTOUR, CASE: CLASSROOM-STUDIO, FLOOR 6th BUILDING C, UNIVERSITAS TRISAKTI - Filea Martha Budiarti; Popi Puspitasari; Khotijah Lahji (International Journal on Livable Space, 2022)
The room requires specific lighting according to its function. One way to achieve the room's optimal comfort is to adjust the natural or artificial lighting to the required standards. This research aims to study daylight intensity in the architectural classroom studio on the sixth floor of Building C Universitas Trisakti and compare it with the illuminance level requirements stipulated in SNI 6197: 2011. This study hypothesizes that the natural intensity of the room, which also functions as an architectural drawing studio, is incompatible with conventional lectures. The measuring instrument was the Lutron LM 8000A Light Lux Meter, while the natural lighting contour simulation used Dialux Evo 9. The results show that the measured natural lighting intensity is unevenly distributed. There are bright zones in the room that exceed the standard value of the illuminance level (> 350-750 lux) and dark zones that are below the standard of illuminance (<350-750 lux), with a distance of 0.5 m - 3m from a row of window openings as a source of lighting.